Improved Biotransformation of Platycoside E into Deapiose-Xylosylated Platycodin D by Cytolase PCL5 under High Hydrostatic Pressure - Kyung-Chul Shin (MDPI AG, 2021)
Platycosides are the functional saponins present in balloon flowers that exert diverse biological effects, and which can be further improved by their deglycosylation. Deapiose-xylosylated platycodin D, which is absent in balloon flowers, can be generated only by cytolase PCL5 by acting on platycoside E. To improve cytolase PCL5-catalyzed production of deapiose-xylosylated platycodin D from platycoside E, we explored the use of high hydrostatic pressure (HHP). At an HHP of 150 MPa, the optimal temperature of cytolase PCL5 activity for converting platycoside E into deapiose-xylosylated platycodin D shifted from 50 to 55 °C, and increased the activity and stability of the enzyme by 5- and 4.9-fold, respectively. Under HHP, the enzyme completely converted 1 mM platycoside E into deapiose-xylosylated platycodin D within 4 h, with a 3.75-fold higher productivity than that under atmospheric pressure. Our results suggest that the application of HHP is a potential method for the economical production of platycosides and enzyme-catalyzed biotransformation of functional saponins.